2021
DOI: 10.1111/jnc.15444
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological substrates underlying corpus callosum hypoconnectivity and brain metabolic patterns in the valproic acid rat model of autism spectrum disorder

Abstract: Atypical connectivity between brain regions and altered structure of the corpus callosum (CC) in imaging studies supports the long‐distance hypoconnectivity hypothesis proposed for autism spectrum disorder (ASD). The aim of this study was to unveil the CC ultrastructural and cellular changes employing the valproic acid (VPA) rat model of ASD. Male Wistar rats were exposed to VPA (450 mg/kg i.p.) or saline (control) during gestation (embryonic day 10.5), and maturation, exploration, and social behavior were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…2E-e, f, k, l, p, r). This data rea rms the correlation delineated by Uccelli et al [45] , associating compromised myelination in the corpus callosum with the manifestations of VPA-induced autism.…”
Section: Demyelination Induced By Prenatal Vpa Can Be Restored By Cle...supporting
confidence: 89%
See 1 more Smart Citation
“…2E-e, f, k, l, p, r). This data rea rms the correlation delineated by Uccelli et al [45] , associating compromised myelination in the corpus callosum with the manifestations of VPA-induced autism.…”
Section: Demyelination Induced By Prenatal Vpa Can Be Restored By Cle...supporting
confidence: 89%
“…The autistic phenotype observed in offspring following prenatal VPA exposure has been linked to dysmyelination in various brain regions, including the medial prefrontal cortex, pyriform cortex, basolateral amygdala, and corpus callosum [30,44,45] . Myelination in the corpus callosum in mice commences postnatally, reaching its peak between 4 and 6 weeks [46] .…”
Section: Demyelination Induced By Prenatal Vpa Can Be Restored By Cle...mentioning
confidence: 99%
“…Moreover, OCD-like behavior mice exhibited increased c-fos expression in the AC ([ 80 ]. In contrast, in a previous study in our laboratory we found that HD rats selected by SIP showed reduced myelin basic protein (MBP) in the CC [ 61 ], as well as in a preclinical model of ASD [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, a study reported a decrease in myelin content but a preserved population of OL cells in the corpus callosum at PND15. However, there was a consistent disruption observed in myelin content, number of myelinated axons, and OL population from PND15 to PND36 [ 312 ]. These stages in rats are similar to the infant and juvenile stages of human development [ 197 ].…”
Section: Vpa and Disruption Of Brain Developmentmentioning
confidence: 89%